Epidemiology and Susceptibility Profile of Aspergillus Species: An Experience from Tertiary Care Hospital - Gulshan Munir, Sadia Farhad, Shaista Alam, Asma Azim, Saman Hussain, Sikandar Ali Khan, Khadija Raziq, Sudhair Abbas Bangash, Inam-U-Llah, Hina Mir (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The primary emphasis of our research is on people with hematologic malignancies, and we want to learn more about the features of clinical and environmental Aspergillus isolates by doing so. Study Design: Prospective study Place and Duration: This study was carried out at Department of Pathology, Mardan Medical Complex from October 2021 to March 2022 Methods: There were 160 patients of both genders included in this study. Included patients were aged between 18-80 years. Patients with hematologic malignancy were included. Invasive aspergiluus isolates from all patients in which 80 were clinical and 80 were environmental. . With the help of SPSS 22.0, clinical data were analyzed and Aspergillus species-level cryptic identification, antifungal susceptibilities, and cyp51 gene sequencing were all carried out. Results: Among 160 included patients, majority of the cases 95 (59.4%) were males and 65 (40.6%) patients were females. We found that 75 (46.9%) cases had age >50 years. Most common diagnostic criteria were probable IA found in 140 (87.5%) cases. Co-morbidities were pulmonary disease, neurological disease, autoimmune disease, cardiac disease and burns. Cryptic Aspergillus species composed 37.5% of environmental and clinical isolates. Section Nigri had a significant value (70.5%) of cryptic species, mostly among A. awamori and A. tubingensis the former was prevalent in ambient samples and the latter in clinical isolates (P 0.003). Twelve (7.5%) of 80 A. fumigatus isolates were azole resistant. At 90 days, A.fumigatus was 100% responsible for all deaths by resistant to azoles. Conclusion: Comparing clinical and environmental isolates, this study reveals a large proportion of cryptic Aspergillus species, highlights the clinical consequences of azole resistance. Keywords: Hematologic Malignancy, Drug Resistance Mechanisms, Aspergillus, Environmental Microbiology, Azoles